Technical report : issues and strategies of e-learning - T., Kanendran; Savarimuthu, Johnny *; Burra, Venkata Durga Kumar * (Sunway University College, 2004)
An effective e-learning system involves a systematic process of planning, design, development, evaluation, and implementation of a meaningful learning environment where learning is fostered and supported. While there still exists some uncertainty about its role in education and professional training, there is a growing concern about the issues and strategies of e-learning that may be faced by both providers and learners of e-learning in future. This technical report addresses some of the main issues and strategies that are currently encountered in e-learning.